Impact Evaluation of Community Sport Programmes and “Sport Social Work Practices” - Kirsten Verkooijen; Pascal Delheye (Social Inclusion)
Initiatives that employ sport as a means to achieve social objectives span a broad spectrum—from those primarily centred on sporting activities to those closely aligned with principles of social work. This thematic issue, titled “Impact Evaluation of Community Sport Programmes and ‘Sport Social Work Practices,’” reflects this diversity in both terminology and approach. It brings together twelve original contributions that critically examine the design, implementation, and evaluation of such initiatives. Drawing on case studies, literature reviews, and conceptual analyses from a range of global contexts, the issue offers a multifaceted perspective on the role of sport as a catalyst for social change. Particular attention is given to how the impacts of these initiatives can be more effectively understood, assessed, and sustained. The wide range of research questions, programme types, methodological approaches, and target populations underscores the complexity and scope of this interdisciplinary field. Collectively, the contributions demonstrate the potential of sport to serve as a meaningful vehicle for personal and social development, particularly when initiatives or interventions are locally embedded, relationally oriented, and grounded in the lived experiences of participants.